Pengaruh Durasi Static Stretching Otot Hamstring Terhadap Peningkatan Ekstensi Sendi Lutut Pada Lanjut Usia Di Posyandu Serangan Desa Blulukan - Sugiarto, Arif; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2017)
Background: The process of aging affects changes to all systems of the body, one of which changes in the musculoskeletal system. The hamstring muscles are the muscles that easy decreased flexibility, given the characteristics of type I muscle that are difficult to return to forms previously. To improve the extension of the knee joint and minimize the loss of muscle flexibility should be given static stretching exercises. Purpose: To identify the difference between the duration of static stretching the hamstring muscles for 30 seconds and 60 seconds to increase the extension of the knee joint in the elderly. Methods: This study is a quasi experimental research design "Two Group Pre test and Post test". The first group was given static stretching with a duration of 30 seconds and the second group with a duration of 60 seconds. The number of respondents in this study is 16 people, with purposive sampling technique sampling with due regard to inclusion and exclusion criteria. This research was conducted with a frequency 4minggu 3x / week. Results: Based on the Wilcoxon test on static stretching duration of 30 seconds was obtained p = 0.012 and the duration of 60 seconds was obtained value of p = 0.011. The result of different influences with Mann Whitney test obtained by value p = 0.491. Conclusion: Static stretching is proven to increase the extension of the knee joint in the elderly. Static stretching duration between 30 seconds and 60 seconds there is no significant difference effect Keywords: duration of static stretching, hamstring muscles, knee joint extension, elderly